Influência da posição de aplicação de carga no defeito ósseo e da distância dos suportes no teste de flexão de três pontos da tíbia de rato: análise experimental e de elementos finitos - Gonzalez Osuna, Luis Gustavo (2019)
Different biomechanical methods can be used to characterize the structural properties of the bone, and the three-point bending test is the most used method, but it experiences a variability of the parameters during its execution, so a consensus and standardization of the test is necessary. In this sense, the objective of this study was to define, through experimental and finite element analysis, methodological parameters for the evaluation of bone repair of monocortical defects in the proximal metaphysis of the tibia of rats. Bone defects were created in 60 tibias of male Wistar rats. The animals were euthanized 7 days after surgery. Five specimens were used to create 3D models for finite element analysis. The three-point bending test (n = 10) and the finite element analysis (n = 5) were two spam distances: 6 and 10mm; and three position of the bone defect in relation to the load application tip: up, front and down. The null hypothesis tested was that the distance of the supports and the position of the defect had no influence on the biomechanical behavior of the bone during the presentation of the three point flexion test. The results demonstrated that the distances of the supports and the variation of the position of the bone defect during the application of the load had a significant influence on the biomechanical behavior of the bone in the three-point bending test.